PENGEMBANGAN POTENSI DAN PEMBERDAYAAN MASYARAKAT DESA MENDOYO DAUH TUKAD KABUPATEN JEMBRANA - Atmika, I. K. A.; Suriadi, I. G. A. K. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
Mendoyo Dauh Tukad village located in the district Mendoyo, Jembrana Regency of Bali province, including areas that have fertile land for agriculture with an average temperature of the village is 28o C - 30o C which is good for a variety of crops. In addition to a potential agricultural area is also a great area to be used as breeding areas to help improve the economy. Thus this village is a rural area that is fertile and rich in agriculture products, but everything is not fully utilized, therefore the necessary breakthrough to process the natural resources. Gapoktan oyster mushroom cultivators constrained conditions of temperature and humidity in the mushroom house, so messelium do not grow well. Many straw that should be processed into animal feed alternative. Livestock manure has the potential to be processed into organic fertilizer and biogas. The PENGEMBANGA POTENSI DAN PEMBERDAYAAN MASYARAKAT DESA MENDOYO DAUH TUKAD KABUPATEN JEMBRANA 98 | JURNAL UDAYANA MENGABDI purpose of KKN PPM activities in the village Mendoyo Dauh Tukad is empowering communities in exploring the potential of the territory, to overcome the things mentioned above. Methods of implementation activities are divided into three stages. The first stage is the preparation and debriefing, the second phase of implementation of activities in the field, and the third stage of evaluation and monitoring for correction and improvement of the sustainability of the program. The preparation phase begins with the supervisor and the student court hearings with village officials and community leaders to determine the scale of priority actions based on the conditions and the potential that exists in the community, this event was held on July 9 2015.Tahap implementation of the activities carried out by counseling and practice in the field , as well as mentoring by students participating in service learning while in the field. Service activities carried out for one month starting on August 1, 2015 until August 30, 2015. The third phase is the evaluation and monitoring is done by the implementation team or field supervisor and coordinator of corruption to see the impact and sustainability of programs that have been implemented.
Keywords: potential, oyster mushrooms, messelium, biogas, organic fertilizers